Quantum computation in algebraic number theory: Hallgren’s efficient quantum algorithm for solving Pell’s equation - Jozsa, Richard (Annals of physics, 2003)
Pell’s equation is x 2− dy 2=1, where d is a square-free integer and we seek positive integer solutions x, y>0. Let ( x 0, y 0) be the smallest solution (i.e., having smallest A=x 0+y 0 d ). Lagrange showed that every solution can easily be constructed from A so given d it suffices to compute A. It is known that A can be exponentially large in d so just to write down A we need exponential time in the input size log d . Hence we introduce the regulator R=ln A and ask for the value of R to n decimal places. The best known classical algorithm has sub-exponential running time O( exp log d , poly(n)) . Hallgren’s quantum algorithm gives the result in polynomial time O( poly( log d), poly(n)) with probability 1/ poly( log d) . The idea of the algorithm falls into two parts: using the formalism of algebraic number theory we convert the problem of solving Pell’s equation into the problem of determining R as the period of a function on the real numbers. Then we generalise the quantum Fourier transform period finding algorithm to work in this situation of an irrational period on the (not finitely generated) abelian group of real numbers. This paper is intended to be accessible to a reader having no prior acquaintance with algebraic number theory; we give a self-contained account of all the necessary concepts and we give elementary proofs of all the results needed. Then we go on to describe Hallgren’s generalisation of the quantum period finding algorithm, which provides the efficient computational solution of Pell’s equation in the above sense.